The latest reports on biomarkers used in the diagnosis of ovarian cancer - Chałupnik, Aleksandra; Chilimoniuk, Zuzanna; Dobosz, Maciej; Sobstyl, Anna; Sobstyl, Małgorzata (Journal of Education, Health and Sport, 2022)
Introduction: Ovarian cancer ranks seventh in terms of incidence and eighth in terms of mortality among women worldwide. It is divided into several subtypes. The epithelial type of ovarian cancer is responsible for 90% of cases. The clinical picture is usually an appendage tumor detected by palpation or during pelvic imaging. Symptoms are usually non-specific such as abdominal pushing or bloating. State of knowledge: Ovarian cancer is usually detected at an advanced stage due to the long duration of absence of symptoms. Therefore, there is an urgent need to look at existing and identify potential biomarkers that can lead to the development of new and more effective predictors for the diagnosis and prognosis of ovarian cancer. The ability of these biomarkers to predict the existence and stages of ovarian cancer could improve early diagnosis and survival of ovarian cancer patients. Currently, the biomarkers CA-125 and HE4 play the most important role in diagnosis. However, there are an increasing number of reports on other biomarkers such as kallikreins, bikunin, VEGF, and mesothelin. Summary: Partly due to the lack of effective screening, ovarian cancer is usually diagnosed in the final stages. This is why ongoing research into new biomarkers that could contribute to faster detection of the disease is so important. They would also increase the effectiveness of the therapies used and enable a better prognosis of the course of the disease.